Study of the effectiveness of constructive methods through the evaluation of the surface using the LVC method: Case study of the Antônio Carlos Belchior highway in the city of Sobral, CE - Liberato, Lauanda de Sousa; Holanda, Roberto Pimentel; Lopes, Elis Ferreira; Pereira, Mauricio de Sousa; Vasconcelos, Jose Osmildo (Seven Editora, 2023)
Transport infrastructure plays a crucial role in the socio-economic development of a country both at regional and national levels. However, this segment faces difficulties to develop essential activities that can offer differentiated support in the transport sector. The main difficulties are related to the lack of permanent investments in the construction, maintenance, and inspection of highways. The present research work had as its main focus to evaluate the surface conditions of the pavement of a highway using a Continuous Visual Survey Method. For this purpose, a comparative analysis was carried out between the project of the enterprise and its execution, as well as the pathologies presented as a result of its use. The studied highway, named Av. Antônio Carlos Belchior, is located in the city of Sobral, Ceará, Brazil. For the evaluation of the surface of the pavement, the Norm DNIT 008/2003 - PRO was adopted, where the required conditions for the accomplishment of the evaluation of the surface of flexible and semi-rigid pavements are fixed. During the work, the pathologies present in the pavement were detected and classified according to the characteristics presented during the evaluation. Therefore, in this work, an approach was carried out from the elaboration of the project to the execution of the highway, analyzing the factors that contributed to the wear and/or emergence of pathologies. The Continuous Visual Survey Method made it possible to diagnose the critical points of the highway from the pathologies detected during the evaluation process. DOI:https://doi.org/10.56238/alookdevelopv1-030